The Meaning of Local Culture in Industrial Relations: A Qualitative Study in the Makassar Community Work Environment - Kurniawan, Agung Widhi (Maksimal Jurnal : Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
This narrative inquiry explores the resurgence of local heritage brands among urban millennial consumers in Java, Indonesia, examining nostalgia as a primary emotional driver of purchasing behavior. Through in-depth interviews with 30 participants across five major Javanese cities (Jakarta, Bandung, Semarang, Yogyakarta, Surabaya), supplemented by sensory elicitation techniques, the study reveals how heritage consumption functions as temporal integration weaving personal nostalgia (e.g., childhood memories evoked by jamu’s bitterness or batik’s texture) with constructed cultural heritage. Findings identify a nuanced authenticity paradox: participants demanded visible craftsmanship as proof of intergenerational integrity while strategically embracing modernization that preserves cultural essence. Heritage brands emerged as tools for hybrid identity work, enabling millennials to reclaim Javanese identity within globalized selves through embodied rituals (e.g., lulur skincare as cultural homage). The emotional landscape featured reflective nostalgia, bittersweet resonance, balancing comfort with awareness of cultural transformation, and transforming consumption into agentive cultural resilience. Ultimately, purchasing decisions represent ethical stewardship, sustaining intangible heritage through market mechanisms ("buying time for traditions"). The study contributes to consumer culture theory by reframing nostalgia as a dynamic social force that bridges personal memory, cultural preservation, and marketplace action in postcolonial urban contexts.